The Dopamine D5 Receptor Is Involved in Working Memory - Carr, Gregory V.; Maltese, Federica; Sibley, David R.; Weinberger, Daniel R.; Papaleo, Francesco (Frontiers in Pharmacology, 2017)
Pharmacological studies indicate that dopamine D1-like receptors (D1 and D5) are critically involved in cognitive function. However, the lack of pharmacological ligands selective for either the D1 or D5 receptors has made it difficult to determine the unique contributions of the D1-like family members. To circumvent these pharmacological limitations, we used D5 receptor homozygous (-/-) and heterozygous (+/-) knockout mice, to identify the specific role of this receptor in higher order cognitive functions. We identified a novel role for D5 receptors in the regulation of spatial working memory and temporal order memory function. The D5 mutant mice acquired a discrete-paired trial variable-delay T-maze task at normal rates. However, both D5+/- and D5-/- mice exhibited impaired performance compared to D5+/+ littermates when a higher burden on working memory faculties was imposed. In a temporal order object recognition task, D5+/- exhibited significant memory deficits. No D5-dependent differences in locomotor functions and interest in exploring objects were evident. Molecular biomarkers of dopaminergic functions within the prefrontal cortex (PFC) revealed a selective gene-dose effect on Akt phosphorylation at Ser473 with increased levels in D5-/- knockout mice. A trend towards reduced levels in CaMKKbeta brain-specific band (64 kDa) in D5-/- compared to D5+/+ was also evident. These findings highlight a previously unidentified role for D5 receptors in working memory function and associated molecular signatures within the PFC.